Minerals and Cucumbers in the Sea: International relations will transform the Tongan state - Brown Pulu, Teena (Te Kaharoa, 2014)
<span style="color: #111111; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 11.2px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; display: inline !important; float: none;">Constitution law researcher Guy Powles, a Pakeha New Zealander residing in Australia was not optimistic accurate predictions on “the [Tonga] election which is coming up now in November” could be made (Garrett, 2014). “A man would be a fool to try to guess just where the balance will finish up,” he uttered to Jemima Garrett interviewing him for Radio Australia on April 30th 2014 (Garrett, 2014). Picturing the general election seven months away on November 27th 2014, Powles thought devolving the monarch’s executive powers to government by constitutional reform was Tonga’s priority. Whether it would end up an election issue deciding which way the public voted was a different story, and one he was not willing to take a punt on. <span style="color: #111111; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 11.2px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; display: inline !important; float: none;">While Tongans and non-Tongan observers focused attention on guessing who would get into parliament and have a chance at forming a government after votes had been casted in the November election, the trying political conditions the state functioned, floundered, and fell in, were overlooked. It was as if the Tongans and <em style="color: #111111; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 11.2px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff;">Palangi <span style="color: #111111; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 11.2px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; display: inline !important; float: none;">(white, European) commentators naively thought changing government would alter the internationally dictated circumstances a small island developing state was forced to work under.